Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.11591/ijai.v12.i1.pp402-414
|View full text |Cite
|
Sign up to set email alerts
|

Survey of indoor tracking systems using augmented reality

Abstract: <p><span lang="EN-US">Augmented reality overlays virtual content on the physical world, displaying location-based information more efficiently. Tracking is a trace detail of the location recorded, either by taking a reading based on a set time interval, set distance, and change in direction by more than a certain angle, or a combination of these. Tracking is divided into two types, outdoor tracking, and indoor tracking. Augmented reality added value and information to tracking applications, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Komianos [26] also indicated that AR is easy to employ in museums compared to Virtual Reality (VR) and Mixed Reality (MR) because it is mostly based on the Bring Your Own Device (BYOD) concept as it reduces costs and is easier for users to handle their own device. The survey by Shewail et al [27] revealed that, for the purpose of indoor tracking, communication technology-based tracking can be faulty for applications that need accurate tracking and registration, while image-based tracking can be more accurate and reliable. However, they also pointed out the scalability problems of image-tracking-based solutions.…”
Section: Image-tracking-based Indoor Navigationmentioning
confidence: 99%
“…Komianos [26] also indicated that AR is easy to employ in museums compared to Virtual Reality (VR) and Mixed Reality (MR) because it is mostly based on the Bring Your Own Device (BYOD) concept as it reduces costs and is easier for users to handle their own device. The survey by Shewail et al [27] revealed that, for the purpose of indoor tracking, communication technology-based tracking can be faulty for applications that need accurate tracking and registration, while image-based tracking can be more accurate and reliable. However, they also pointed out the scalability problems of image-tracking-based solutions.…”
Section: Image-tracking-based Indoor Navigationmentioning
confidence: 99%